Multi-frame rate plane wave contrast-enhanced ultrasound imaging for tumour vascular imaging and perfusion quantification - Leow,CH; Braga,M; Hernandez-Gil,J; Long,NJ; Aboagye,EO; Tang,MX (IEEE, 2017)
Angiogenesis and blood flow dynamics play an important role in the development of malignant tumours and their response to treatment. While contrast enhanced ultrasound (CEUS) imaging with microbubble contrast agents as a tool for imaging angiogenesis and flow dynamics has shown great potential [1], recent development of plane wave high frame-rate (HFR) CEUS has offered new opportunities in such applications. In this study, we demonstrate an interleaved multi-frame rate plane wave CEUS imaging to quantify perfusion and to image vascular structure with improved resolution and contrast.